Pengaruh Rating, Review, dan Response Penjual terhadap Kepercayaan dan Minat Beli Pengguna Shopee Se-Karesidenan Besuki - Haris Haris; Nelly Oktavia Adiwijaya; Qurrota A'yuni Ar Ruhimat (INFORMAL: Informatics Journal, 2022)
There are many fake ratings and reviews to increase positive income which is basically unknown for sure whether it affects buying interest and buyer trust. This research wanted to find out the effects of ratings, reviews and seller response on buying interest and buyer trust of the Besuki residency community towards the Shopee application. There were 349 respondents, with 20 instruments distributed and processed. There were 7 hypotheses proposed and the result showed that all of the hypothesis is accepted and it can be concluded that the seller's rating, review and response have a positive and significant effect on buying interest and buyer trust towards the Shopee application.